Factors affecting progression-free survival in non-HIV-related Kaposi sarcoma. (3rd May 2016) - Sen, Fatma; Tambas, Makbule; Ciftci, Rumeysa; Toz, Bahtiyar; Kilic, Leyla; Bozbey, Hamza U.; Karanlik, Hasan; Kurul, Sidika; Vatansever, Sezai; Oral, Ethem N.; Saglam, Esra K.; Kizir, Ahmet; et al.
Abstract: Background : Non-HIV related Kaposi sarcoma (NHKS) is a rare indolent neoplasm which is more common around Mediterranean origin. Data concerning factors that influence progression-free survival (PFS) for NHKS are insufficient. The purpose of present retrospective analysis was to distinguish the factors affecting PFS in patients with NHKS. Methods : A hundred and twenty-eight consecutive patients with NHKS who were treated or observed between 1997 and 2014 at Istanbul University Institute of Oncology were included into the study. Treatment response and progression definitions were determined according to different treatment modalities administered at first line. Results : Majority of patients were male ( n = 97, 75.8%). Median age of the whole group was 66 years (28–85). Of the patients, 15 patients were immunosuppressant, whereas 113 patients had no disease that caused immunosuppression. Patients were treated with local excision ( n = 57, 44.5%), chemotherapy ( n = 32, 25.0%) and/or radiotherapy ( n = 13, 10.2%) or observed without treatment ( n = 26, 20.3%). At a median follow-up of 28 months, 71 (55.5%) patients had progression, while 3 patients (2.3%) died of NHKS. On univariate analysis, patients who had hypertension (HT) had poorer PFS compared with others (19 ± 12 versus 41 ± 22 months; p = 0.03), whereas plaque formation was associated with better outcome (25 ± 9 versus 54 ± 12 months; p = 0.03). In addition, heavy smoking (≥40 pack-years) had a borderline significance regarding better PFS time (23 ± 24 versus 45 ± 38 months, p = 0.06). On multivariate analysis, none of factors evaluated had any impact on PFS. Conclusions : HT was correlated with poorer outcome among NHKS patients. Patients with plaque formation and ≥40 pack-years of smoking had better PFS than others.